A chiral self-sorting photoresponsive coordination cage based on overcrowded alkenes - Constantin Stuckhardt; Diederik Roke; Wojciech Danowski; Edwin Otten; Sander J. Wezenberg; Ben L. Feringa (Beilstein Journal of Organic Chemistry, 2019)
In recent years, increasing efforts have been devoted to designing new functional stimuli-responsive supramolecular assemblies. Here, we present three isomeric supramolecular coordination complexes consisting of a Pd2L4 stoichiometry. As shown by NMR, CD and X-ray studies, as well as DFT calculations, these complexes form cage-like structures by chiral self-sorting. Photochromic ligands derived from first generation molecular motors enable light-driven interconversion between the three isomers. Two of the isomers were able to form host–guest complexes opening up new prospects toward stimuli-controlled substrate binding and release.